ASME 2019 International Technical Conference and Exhibition on Packaging and Integration of Electronic and Photonic Microsystem 2019
DOI: 10.1115/ipack2019-6568
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Immersion Cooling on Thermo-Mechanical Properties of PCB’s and Reliability of Electronic Packages

Abstract: Immersion cooling is highly efficient thermal management technique and can potentially be used for thermal management of high-density data. However, to use this as a viable cooling technique, the effect of dielectric coolants on the reliability of server components needs to be evaluated. Previous work reported contradicting findings for Young’s modulus of PCBs, providing motivation for this work. This study focuses on effect of immersion cooling on the mechanical properties of printed circuit board (PCB) and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Although there is a large amount of literature on thermal immersion cooling and cost savings, there is little literature on the impact of immersion cooling on the reliability of information technology (IT) equipment such as PCBs and electronic packages. Ramdas et al [49], focusing on the change of thermo-mechanical properties of PCBs when immersed in dielectric fluid and the effect of the change on the reliability of electronic packages, showed that Young's modulus is decreasing for PCBs after immersion in dielectric coolant, which is likely to increase the reliability of electronics packages. Moreover, research by Muslim [50] using a variety of dielectric liquids has demonstrated that the dielectric properties are satisfactorily stable and undergo minimal change over time, even when exposed to high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is a large amount of literature on thermal immersion cooling and cost savings, there is little literature on the impact of immersion cooling on the reliability of information technology (IT) equipment such as PCBs and electronic packages. Ramdas et al [49], focusing on the change of thermo-mechanical properties of PCBs when immersed in dielectric fluid and the effect of the change on the reliability of electronic packages, showed that Young's modulus is decreasing for PCBs after immersion in dielectric coolant, which is likely to increase the reliability of electronics packages. Moreover, research by Muslim [50] using a variety of dielectric liquids has demonstrated that the dielectric properties are satisfactorily stable and undergo minimal change over time, even when exposed to high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…But why it is not deployed in today's typical data centers? Maintenance and reliability, and specifically the lack of practical information on these aspects, are the primary concerns for adapting immersion cooling technologies [15], [16], [17], [18], [19], [20]. Increased number of IT equipment failures, liquid leakage, and liquid evaporation are the main challenges associated with its maintenance procedure, which also impose additional operational costs.…”
Section: Introductionmentioning
confidence: 99%